2017
DOI: 10.3892/mmr.2017.6698
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid prevents inflammatory responses in IL-1β-stimulated human SW-1353 chondrocytes, a model for osteoarthritis

Abstract: Chlorogenic acid (CGA), which is a natural compound found in various plants, has been reported to exert notable anti‑inflammatory activities. The present study investigated the effects and underlying mechanism of CGA on interleukin (IL)‑1β‑induced osteoarthritis (OA) chondrocytes. An in vitro OA‑like chondrocyte model was established using IL‑1β‑stimulated human SW‑1353 chondrocytes. Cell viability was assessed using an MTT assay. Nitric oxide (NO) and IL‑6 production were evaluated by Griess reaction and ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 37 publications
1
30
0
2
Order By: Relevance
“…2). For the first time, the presence of eupafolin 7-O-glucoside (12) in Arnica montana, as well as kaempferol 3-acetylglucoside (28) and luteolin 3í-O-glucoside (25) was indicated (Fig. 2).…”
Section: Identification Of Flavonoidsmentioning
confidence: 90%
See 1 more Smart Citation
“…2). For the first time, the presence of eupafolin 7-O-glucoside (12) in Arnica montana, as well as kaempferol 3-acetylglucoside (28) and luteolin 3í-O-glucoside (25) was indicated (Fig. 2).…”
Section: Identification Of Flavonoidsmentioning
confidence: 90%
“…Additionally, it was reported that 5-CQA and cynarin had a protective effect against t-BOOH-induced ROS generation in HepG2 cells (23). It was also stated, that 5-CQA prevents inflammatory responses in IL-1‚-stimulated human SW-1353 chondrocytes, a model for osteoarthritis (24,25). Arnica flower flavonoids are involved in the anti-inflammatory action of this plant raw material, inhibiting the activity of pro-inflammatory mediators COX, 5-LOX, and hyaluronidase and elastase enzymes (8,10).…”
mentioning
confidence: 99%
“…Cartilage abnormity is a key link in the pathogenesis of OA, and closely related the mechanical properties, cartilage cell proliferation and apoptosis, inflammatory factor and the secretion of MMPs (23). It has been reported that IL-1β can stimulate the release of NO from the cartilage cells so as to promote apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that IL-1β can stimulate the release of NO from the cartilage cells so as to promote apoptosis. Inflammatory factor and its harm are important mechanisms of OA (23). In the process of OA, the pathological changes of cartilage tissue can lead to the increase of inflammatory factor expression, while the increased inflammatory factors in turn intensify the cartilage tissue lesions by mediating signal activities, forming a vicious circle (24).…”
Section: Discussionmentioning
confidence: 99%
“…29 CGA'nın interlökin-1beta (IL-1�) ile uyarılmış insan kondrosit hücre hattında (SW-1353) infl amatuar yanıtları önlediği rapor edilmiştir. 30 CGA, metotreksat ile indüklenmiş karaciğer hasarına karşı metotrekrat ile azalan SOD, katalaz (CAT) gibi antioksidanlar arttırarak antioksidan özelliği sayesinde hepatoprotektif etki göstermiştir. 31 Yüksek yağlı diyetle beslenen sıçanlara CGA uygulamasının karaciğer ve böbreklerde antioksidan durumu arttırdığı, yüksek dansiteli lipoprotein (HDL) miktarını arttırdığı ve insulin miktarını azalttığı gösterilmiştir.32 CGA'nın, fosfaIdilinositol 3-kinaz/protein kinaz aracılı (PI3K/Akt) nükleer faktör E2-ilişkili faktör 2/hem oksijenaz-1 (Nrf2/HO-1) yolağının aktivasyonu yoluyla hidrojen peroksit kaynaklı oksidatif hasara karşı fare kalvarisi kaynaklı hücre hattını (MC3T3-E1) korumuş olduğu ve osteoporoz tedavisinde etkili bir ilaç olabileceği gösterilmiştir.…”
Section: Tas Reaktif Oksijen Türlerini Temiz-unclassified